Development of a loop‐mediated isothermal amplification assay for rapid and simple detection of Erysipelothrix rhusiopathiae. (11th December 2013) - Yamazaki, Y.; Oba, E.; Kashiwagi, N.; Sugita, K.; Shiiba, K.; Baba, Y.; Shimoji, Y.; Yamazaki, W.
<x xml:space="preserve">Abstract</x> Abstract Erysipelothrix rhusiopathiae is a causative agent of swine erysipelas. We developed a novel and highly specific loop‐mediated isothermal amplification (LAMP) assay for sensitive and rapid detection of E. rhusiopathiae. The LAMP assay correctly detected 39 E. rhusiopathiae strains. No LAMP products were detected from 14 non‐rhusiopathiae Erysipelothrix and 16 non‐Erysipelothrix strains, including E. tonsillarum serovar 10 strains, which are difficult to be discriminated from E. rhusiopathiae strains. These results were consistent with those obtained by a conventional E. rhusiopathiae‐specific PCR assay. Starting with DNA extraction from a single colony, the gel‐based PCR assay took 4 h to provide a result, but the LAMP assay was faster, requiring only 37–80 min. The conventional culture test required more than 3–4 days to isolate and identify E. rhusiopathiae in the enrichment cultures. In contrast, the LAMP assay required less than 22 h from the beginning of the enrichment culture to final determination. These results suggest that the LAMP assay is useful as an adjunct to facilitate early diagnosis of swine erysipelas. Significance and Impact of the Study This is the first report of a loop‐mediated isothermal amplification (LAMP) assay for simple and cost‐effective detection of E. rhusiopathiae from swine samples. The LAMP assay provided more rapid detection of the bacterium than conventional PCR and biochemical‐based assays, and it may potentially facilitate surveillance and early diagnosis of swine erysipelas in the field.